PENGARUH WORK-LIFE BALANCE TERHADAP MOTIVASI DAN LOYALITAS KARYAWAN PT SUMBER ALFARIA TRIJAYA TBK (ALFAMART) - Rofik Priyanto; Yusuf Ramadhan (POLITEKNIK LP3I JAKARTA, 2025)
Human resources are a key factor in determining the success of an organization, including in a competitive retail industry such as PT Sumber Alfaria Trijaya Tbk (Alfamart). This study aims to analyze the effect of work-life balance and work motivation on employee loyalty at Alfamart Area Purbalingga. The phenomena that occur indicate a decrease in work enthusiasm, lateness, and lack of sense of responsibility which are thought to be caused by an imbalance between work and personal life and low work motivation. This study uses a quantitative approach with a survey method through a questionnaire to 76 of the total 157 employees as a sample. Data analysis techniques are carried out using a Likert scale and descriptive statistical calculations. The results of initial observations indicate that the lack of appreciation and workload outside of working hours have an impact on low loyalty. It is hoped that the results of this study can contribute to management in designing strategies to increase employee loyalty through the implementation of work-life balance programs and providing effective work motivation. Thus, the company is able to retain high-performing employees and support the achievement of organizational goals in a sustainable manner